Glycogen synthase kinase 3 beta alters anxiety-, depression-, and addiction-related behaviors and neuronal activity in the nucleus accumbens shell. (1st May 2017) - Crofton, Elizabeth J.; Nenov, Miroslav N.; Zhang, Yafang; Scala, Federico; Page, Sean A.; McCue, David L.; Li, Dingge; Hommel, Jonathan D.; Laezza, Fernanda; Green, Thomas A.
Abstract: Psychiatric disorders such as anxiety, depression and addiction are often comorbid brain pathologies thought to share common mechanistic biology. As part of the cortico-limbic circuit, the nucleus accumbens shell (NAcSh) plays a fundamental role in integrating information in the circuit, such that modulation of NAcSh circuitry alters anxiety, depression, and addiction-related behaviors. Intracellular kinase cascades in the NAcSh have proven important mediators of behavior. To investigate glycogen-synthase kinase 3 (GSK3) beta signaling in the NAcSh in vivo we knocked down GSK3beta expression with a novel adeno-associated viral vector (AAV2) and assessed changes in anxiety- and depression-like behavior and cocaine self-administration in GSK3beta knockdown rats. GSK3beta knockdown reduced anxiety-like behavior while increasing depression-like behavior and cocaine self-administration. Correlative electrophysiological recordings in acute brain slices were used to assess the effect of AAV-shGSK3beta on spontaneous firing and intrinsic excitability of tonically active interneurons (TANs), cells required for input and output signal integration in the NAcSh and for processing reward-related behaviors. Loose-patch recordings showed that TANs transduced by AAV-shGSK3beta exhibited reduction in tonic firing and increased spike half width. When assessed by whole-cell patch clamp recordings these changes were mirrored by reduction in action potential firing and accompanied by decreased hyperpolarization-induced depolarizing sag potentials, increased action potential current threshold, and decreased maximum rise time. These results suggest that silencing of GSK3beta in the NAcSh increases depression- and addiction-related behavior, possibly by decreasing intrinsic excitability of TANs. However, this study does not rule out contributions from other neuronal sub-types. Highlights: Specific knockdown of GSK3 beta in the NAc shell induces an anxiolytic-like effect. Knockdown of GSK3 beta in the NAcSh induces depression-like behavior. Viral-mediated knockdown of GSK3 beta increases cocaine self-administration. Knockdown also reduces spontaneous firing and alters intrinsic excitability of TANs.